Engineering stable insect cell expression systems using site-specific integration technology for production of complex proteins - Dias, Mafalda M (2020)
"Recombinant protein production plays a pivotal role in the industrial manufacturing of therapeutics, vaccines and diagnostics. A variety of expression systems are available, whereby insect High FiveTM (Hi5) cells are one of the main platforms largely due to the development of the baculovirus expression vector system (BEVS). While there are continuous efforts to improve the BEVS, key limitations remain, including the baculovirus-mediated cell lysis and the lack of homogeneous humanized glycosylation. To address these limitations, there is a driving force towards the adoption of virus-free gene expression approaches, notably the use of random or site-specific integration systems (the most widely used technique for stable cell expression from a previously identified and characterized locus)(...)"